Упростите выражение (2a-b)(a+b-c)-(a+2b)(a-b+c)+3c(a+b)

Упростите выражение (2a-b)(a+b-c)-(a+2b)(a-b+c)+3c(a+b)
Гость
Ответ(ы) на вопрос:
Гость
(2a-b)(a+b-c)-(a+2b)(a-b+c)+3c(a+b)=2a²-ab+2ab-b²-2ac+bc-a²-2ab+ab+2b²-ac-2bc+3ac+3bc=a²+b²+2bc
Гость
[latex](2a-b)(a+b-c)-(a+2b)(a-b+c)+3c(a+b)= \\ 2 a^{2} -ab+2ab- \\ -b^{2} -2ac+bc-a^{2}-2ab+2b^{2} -ac-2bc+3ac+3bc \\ = a^{2} +b^{2} +2bc [/latex] Раскрывали скобки и применяли формулы сокращенного умножения;) 
Не нашли ответ?
Ответить на вопрос
Похожие вопросы